2018
DOI: 10.12963/csd.18469
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Executive Function for Vocabulary Acquisition and Word Learning in Preschool-Age Children with and without Vocabulary Delay

Abstract: This work was supported by BK21plus project by the Korean Government. Objectives: The development of executive function (EF) in childhood can be understood in terms of 'consciousness' development. As age increases, the potential of conscious control of thoughts and behaviors for child can be increased. This study examined the relationship of EF and word learning in children with and without vocabulary delay (VD). Methods: Thirty-five 5-to-6-year-old children with VD and 35 age-matched children with typically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1
7

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 64 publications
0
5
1
7
Order By: Relevance
“…단순언어장애 아동들은 영역-일반적 결함(domain-general deficit)에 의해 언어뿐만 아니라 집행기능에서도 어려움을 가지며 이 에 대해 언어 능력과의 연관성을 밝히고자 현재 활발한 연구가 이 루어지고 있다 (Ebert & Kohnert, 2011;Kapa et al, 2017;Yang & Gray, 2017;Yang & Yim, 2018). 갱신 능력에 관한 선행연구에서는 단순언어장애 아동들이 정보를 유지하고 기억해야 하는 숫자 회 상, 단어 회상, 문장 회상 등의 과제에서 일반 아동들보다 더 낮은 수행력을 보였으며 (Archibald & Gathercole, 2006;Vugs, Hendriks, Cuperus, Knoors, & Verhoeven, 2017) 숫자목록을 기억하고 그것을 역순으로 회상하는 숫자 역순 회상(backward digit span task)에서도 어려움이 나타났다 (Archibald & Gathercole, 2006;Kapa et al, 2017).…”
Section: 위 세 가지 집행기능의 하위 요소에는 선택적 주의집중의 유지능력unclassified
See 1 more Smart Citation
“…단순언어장애 아동들은 영역-일반적 결함(domain-general deficit)에 의해 언어뿐만 아니라 집행기능에서도 어려움을 가지며 이 에 대해 언어 능력과의 연관성을 밝히고자 현재 활발한 연구가 이 루어지고 있다 (Ebert & Kohnert, 2011;Kapa et al, 2017;Yang & Gray, 2017;Yang & Yim, 2018). 갱신 능력에 관한 선행연구에서는 단순언어장애 아동들이 정보를 유지하고 기억해야 하는 숫자 회 상, 단어 회상, 문장 회상 등의 과제에서 일반 아동들보다 더 낮은 수행력을 보였으며 (Archibald & Gathercole, 2006;Vugs, Hendriks, Cuperus, Knoors, & Verhoeven, 2017) 숫자목록을 기억하고 그것을 역순으로 회상하는 숫자 역순 회상(backward digit span task)에서도 어려움이 나타났다 (Archibald & Gathercole, 2006;Kapa et al, 2017).…”
Section: 위 세 가지 집행기능의 하위 요소에는 선택적 주의집중의 유지능력unclassified
“…Continued. (Ford & Milosky, 2008;Norbury & Bishop, 2002;Yun & Kim, 2005) (Ebert & Kohnert, 2011;Kapa et al, 2017;Yang & Gray, 2017;Yang & Yim, 2018 (Ellis et al, 2015;McMurray et al, 2010;Yoon & Yim, 2019). 인간은 담화를 듣고 있 는 상황에서 관련 단어를 들은 후 빠르게 시선을 움직여 관련 물체 에 시선을 고정시키며 청각적 자극에 따라 시선의 고정이 변화된다 (Eberhard, Spivey-Knowlton, Sedivy, & Tanenhaus, 1995;Takacs & Bus, 2018 (Daneman & Carpenter, 1980 (Garon et al, 2008) 안구 운동에는 개인의 관심이 반영된다 (Just & Carpenter, 1980 (Finneran, Francis, & Leonard, 2009 (Garon et al, 2008;Miyake et al, 2000) 일반 아동 집단에 비해 단순언어장애 아동들이 집행기능의 각 요소 간 약한 결합을 보이고 있음을 알 수 있으며 이러한 차이가 단순언어장애 아동의 영역-일반적 결함에 대한 의견에 다시 한 번 힘을 실어준다 (Ebert & Kohnert, 2011;Kapa et al, 2017;Yang & Gray, 2017;Yang & Yim, 2018 (Daneman & Carpenter, 1980;Just & Carpenter, 1992;Yun & Kim, 2005…”
Section: 대한 대상자 정보는unclassified
“…, . (Marton et al, 2014;Yoo & Yim, 2018) (Yang & Yim, 2018). , (Yoo & Yim, 2018;Zelazo & Müller, 2002).…”
Section: 읽기이해에서 집단 간 수행력 차이unclassified
“…Studies showed that children with SLI demonstrated lesser word gain than typically developing (TD) peers in QUIL tasks (Horohov & Oetiing, 2004;Oetting, Rice, & Swank, 1995;Rice et al, 1990;Rice et al, 1992;Rice et al, 1994;Rice & Bode, 1993;Rice & Woodsamll, 1988;Yang & Yim, 2018;Yang, Yim, & Bae, 2015;Yang, Yim, Kim, & Han, 2013;Yim et al, 2015). For instance, Yang and Yim (2018) presented a video that contained novel words throughout the story to 5-and 6-year-old children and conducted the picture comprehension task. Their results showed that children with vocabulary delay demonstrated less word gain than their TD peers.…”
mentioning
confidence: 99%